STUDY OF MAINTENANCE OF UPS EQUIPMENT (UNINTERUPTABLE POWER SUPPLY) WITH FAULT TREE ANALYSIS (FTA) METHOD TO PRODUCE TIMELY POWER SUPPLY AVAILABILITY AT SOEKARNO-HATTA AIRPORT - Kusumawardana, Nofian Sudi; Nusraningrum, Dewi (International Humanities and Applied Science Journal, 2021)
Abstract - UPS (Uninteruptable Power Supply) is equipment that supports the availability of a continuous supply of electricity that will work when the main electricity supply from PLN is off and the secondary power supply (Genset) is not ready to take over the electricity supply. The purpose of this study is to determine which equipment components are the cause of potential UPS equipment damage and provide advice on appropriate maintenance actions for the selected system using the Fault Tree Analysis (FTA) method. The study population was 7 units of UPS Benning with a capacity of 80 kVA located in different places at Soekarno-Hatta Airport. The results showed that the frequent damage was due to dead air conditioning which caused the temperature of the battery room to be high.Â Keywords: Airport, Uninteruptible Power Supply (UPS), Fault Tree Analysis (FTA), proper maintenance